Structural transformation of nascent char during the fast pyrolysis of mallee wood and low-rank coals - Zhang, L.; Li, T.; Quyn, D.; Dong, Li; Qiu, P.; Li, Chun-Zhu (Elsevier, 2015)
The changes in char structure during the fast pyrolysis of three different feedstocks from 600 °C to 1200 °C were investigated. Western Australian Collie sub-bituminous coal, Victorian Loy Yang brown coal and Australian mallee wood were pyrolysed in a wire-mesh reactor at a heating rate of 1000 K s− 1 with holding time ranging from 0 s to 50 s. FT-Raman/IR spectroscopy was used to characterise the structural features of the chars obtained at different temperatures. The combined use of a wire-mesh reactor and an FT-Raman/IR spectrometer has provided significant insights into the rapid changes in the chemical structure of nascent char during fast pyrolysis. Our results indicate that the three fuels began significant ring condensation at different temperatures. Mallee wood showed significant growth of large rings within 1 s holding at 600 °C; however Loy Yang and Collie coals showed significant ring condensation at 800 °C and 900 °C respectively. With increase in temperature to 1000 °C and higher, most ring condensation occurred at < 1 s holding time. The decrease in the intensity of FT-IR spectrum at ~ 1600 cm− 1 confirmed the rapid growth in ring systems at relatively high temperatures.